Food choice motives, overall attitudes and purchase intentions towards fresh fabricated beef at Kuala Terengganu - Tuan Zainazor Tuan Chilek,; Siti Norashikin,; Fisal Ahmad,; Rahijan Abdul Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Fabricated beef was known as a famous ingredient among the community in Kuala Terengganu and there was a few characteristic were chosen when purchasing it. This research is aimed to study consumers’ food choice motives, overall attitude and purchase intention toward fabricating beef meat. The consumer should know the consequences when consumes meat with lack of quality such as the high amount of fat content, non-desired sensory appeal, unknown origin and cost value of the meat plus the consumer also able to identify the part of fabricated beef that give different tenderness to the meat. Less information leads to the difficulty in choosing the best quality of beef in the marketplace. Random sampling and convenience sampling techniques were employed in this survey. Data was collected from 150 respondents through survey. The outcome demonstrates that most of the consumers suffered a positive perception towards food choice motives for fabricating beef. Overall attitudes of consumers purchase fabricated beef when their elemental needs and wants for quality, accessibility, convenience and affordability were met. Intention to purchase the fabricated beef gave positive impact for the future decision making when encounter the same item, especially when the quality equaled the value price.